Possible existence of a third fundamental long-range force. (30th April 2020) - Nakanishi, Noboru; Yoshida, Ritsu
Abstract: It is inferred that, in addition to the Coulomb and Newtonian forces, there should exist a third fundamental long-range force, which acts between intrinsic angular momenta. This inference is based on the quantum Einstein gravity, that is, the manifestly-covariant, BRS-invariant, canonically quantized theory of general relativity. The form of the potential of the third fundamental long-range force is determined by calculating the non-relativistic limit of the Bethe–Salpeter kernel in the lowest-order perturbation theory. The observability of this force is also discussed.